Minimum acceptable diet use and its associated factors among children aged 6-23 in Ghana: a mixed effect analysis using Ghana Demographic and Health Survey - Berhan Tekeba; Belayneh Shetie Workneh; Alebachew Ferede Zegeye; Almaz Tefera Gonete; Gebreeyesus Abera Zeleke; Tadesse Tarik Tamir (Frontiers Media S.A., 2024)
IntroductionInappropriate feeding practices are a major contributor to child malnutrition. To monitor the feeding practices of young children, current and frequent studies are required. However, as far as our searches are concerned, there is a scarcity of up-to-date information on attainment of the minimum acceptable diet and its predictors in the study area. Therefore, this study aimed to assess the magnitude of attainment of the minimum acceptable diet and its associated factors among children aged 6-23 in Ghana by using the most recent data.MethodsSecondary data analysis was conducted based on the demographic and health survey data conducted in Ghana in 2022. A total weighted sample of 2,621 children aged 6-23 months in the 5 years preceding the survey was included in this study. A multi-level logistic regression model was used to identify the determinants of the minimum acceptable diet. The adjusted odds ratio at 95% Cl was computed to assess the strength and significance of the association between explanatory and outcome variables. Factors with a p-value of <0.05 are declared statistically significant.ResultsThe national prevalence of the attainment of the minimum acceptable diet in Ghana was 26.40% (95% CI: 24.82-28.06). Child from mother with higher education (AOR = 1.96; 95% CI: 1.56-3.31) and father with higher education (AOR = 1.59; 95% CI: 1.04-2.41), Children having postnatal visit (AOR = 1.29; 95% CI: 1.03-1.62), being in the child age of 9-11 months (AOR = 2.09; 95% CI: 1.42-5.03) and 12-23 months (AOR = 3.62; 95% CI: 2.61-5.03), being in a middle (AOR = 1.66; 95% CI: 1.14-3.06), and rich wealth quintile (AOR = 2.06; 95% CI: 1.37-3.10), breastfed children (AOR = 3.30; 95% CI: 2.38-4.56), being in a high-community poverty (AOR = 0.65; 95% CI: 0.44-0.96), and being in the Savannah region (AOR = 0.32; 95% CI: 0.16-0.67) were factors significantly associated with the minimum acceptable diet use.ConclusionMany children are still far behind in meeting the minimum acceptable diet in Ghana as per 90% of WHO-recommended coverage. Measures should be taken to optimize the minimum acceptable diet attainment in the country. Thus, policymakers, the government, and other relevant authorities should focus on the early initiation of complementary feeding, the Savannah region, further empowering women, and enhancing breast-feeding and household wealth status.